2020
DOI: 10.1111/jgh.15025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid‐induced macrophage polarization through modulating peroxisome proliferator‐activated receptor‐gamma activity affects hepatic lipid metabolism via a Toll‐like receptor 4/NF‐κB signaling pathway

Abstract: Background and Aim Chronic inflammation links closely to insulin resistance and lipid metabolism in nonalcoholic fatty liver disease (NAFLD). Macrophage M1 activation plays an important role in the initiation and continuing of pro‐inflammatory response of NAFLD. Our study was to investigate whether macrophage M1/M2 polarization switching would affect hepatic inflammation and lipid metabolism through modulation of peroxisome proliferator‐activated receptor‐gamma (PPAR‐γ) activity in vivo and in vitro. Methods R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…The alpha, beta, delta, and gamma 1,3-PPAR genes are expressed in the liver and encode proteins acting as lipid sensors in metabolism [ 65 , 66 ]. PPAR gamma has also been implicated in the M1 to M2 transition of macrophages in response to fatty acids [ 67 ], thereby affecting hepatocyte metabolism by modulating local inflammatory processes. Moreover, the potential regulation of PPAR gamma expression at the DNA levels (through methylation) and the direct role of this regulation in the placenta in fetal growth restriction both suggest a crucial role in the regulation of metabolism after IUGR [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The alpha, beta, delta, and gamma 1,3-PPAR genes are expressed in the liver and encode proteins acting as lipid sensors in metabolism [ 65 , 66 ]. PPAR gamma has also been implicated in the M1 to M2 transition of macrophages in response to fatty acids [ 67 ], thereby affecting hepatocyte metabolism by modulating local inflammatory processes. Moreover, the potential regulation of PPAR gamma expression at the DNA levels (through methylation) and the direct role of this regulation in the placenta in fetal growth restriction both suggest a crucial role in the regulation of metabolism after IUGR [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, rosiglitazone protects against HFD-induced hepatic steatosis and reduces hepatic lipid content by increasing the expression of genes involved in beta-oxidation and decreasing the expression of lipogenic genes. These beneficial effects of rosiglitazone on lipid metabolism are accompanied by a decrease in hepatic M1 macrophages and modulation of the TLR4/NF-κB signaling pathways [368]. In the MCD model, rosiglitazone improves hepatic steatosis, inflammation, and fibrosis and reduces the expression of the HSC activator TGF-β [369].…”
Section: Pparγ Agonistsmentioning
confidence: 99%
“…Indeed, we have previously shown that extracellular vesicles released from steatotic hepatocytes induce an inflammatory response in Kupffer cells and a fibrogenic response in hepatic stellate cells [43]. Direct effects of free fatty acids on Kupffer cells include M1 polarization leading to a pro-inflammatory phenotype [44,45]. Lipotoxicity, defined as a harmful effect of lipid accumulation in non-adipose tissue, is considered a central mechanism in NAFLD progression [46].…”
Section: Lipotoxicity and Oxidative Stressmentioning
confidence: 99%